THE EFFECT OF POP UP BOOK LEARNING MEDIA AND CRITICAL THINKING ON RESULTS STUDENTS LEARNING IPS CLASS V ELEMENTARY SCHOOL - Echa Surya Kunanti; Syarifah Syarifah; Adi Sutopo (Sensei International Journal of Education and Linguistic, 2021)
The research was aimed are to: (1). Knowing the result social studies of students who were taught using pop up book media were higher than of students who were taught using poster media in class V, (2). Knowing the social studies learning outcomes of students who think critically is higher than the social studies learning outcomes of students who think critically low in class V, (3). Knowing the interaction between the use of pop up book learning media, posters and critical thinking on social studies learning outcomes for class V students. This type of research is a research conducted using a quasi-experimental method. The sample in this study were students of class V. The research design used a 2 x 2 factorial design with data analysis techniques using two-way analysis of variance (ANAVA). The results of this study indicate that: (1). The results of the Anova 2x2 test are known to have a value of F = 41,048 with a price of sig = 0.000, so it can be concluded that the social studies learning outcomes of students taught with pop up book media are higher than those of students who are taught using poster media. (2). The results of the Anova 2x2 test showed that the value of F = 45,250 with a price of sig = 0.000, so it was concluded that the results of the social studies learning who had high critical thinking were higher than the social studies learning outcomes of students who had low critical thinking. (3). The results of the Anova 2x2 interaction between the use of pop up book learning media, posters and critical thinking on students social studies learning outcomes are known that F = 4,586 with a price of sig = 0.038, so it can be concluded that there is an interaction between the use of pop up book, poster and critical thinking learning media on students social studies learning outcomes is proven true.